The Belt Road Project as A Triggering Element of the Securitization of the Uyghur Issue - Göktürk Tüysüzoğlu; Selim Kurt (Siyasal: Journal of Political Sciences)
The Xinjiang Uyghur Autonomous Region (XUAR) is considered based on its ethnocultural, religious, and historical diversity. In its national security documents, known as the White Paper, China associates the region with extremism, separatism, and terrorism; and thus recognizes the Uyghurs as a threat. At the crossroads of OBOR’s (One Belt One Road) three separate land corridors, Xinjiang, which has a crucial place in Beijing’s hegemony-building process, is a region regarded critical from a geopolitical and geo-economics perspective. In this context, Beijing securitizes the Uyghurs, with whom China claims that its own values, political goals, and perception of the future are not compatible, from the “threat” point of view. This approach can also be interpreted through the conceptual elements envisaged by the Copenhagen School, such as immigration waves, horizontal and vertical competition, and depopulation.